Sistem Informasi Webstore Online Pada Toko DK Corner Menggunakan Metode Web Design Responsive Bootstrap - Ria Anggraini; Andri Andri (Jurnal Nasional Ilmu Komputer, 2021)
Toko DK Corner is a trading company that specializes in selling women's daily fashion needs. Currently, the DK Corner Store records more than thousands of sales transactions every year, thus requiring the company to be able to provide ordering services for consumers to support better sales and service transactions and of course increase sales profits. The system development method used in system development is Web Engineering. To implement this sales and ordering information system, supporting components are needed in order to work properly. These components include using the PHP programming language (Personal Homepage), Bootstrap Framework and "for data storage using a MySQL database". "The design of this system is expected to help and overcome existing problems so that it can be useful for interested parties". The purpose of this research is expected with the information system is expected to make it easier for companies to promote the products on offer and make it easier to make online sales transactions so that they can be done anytime and safely, and can increase sales.